2021
DOI: 10.1016/j.heliyon.2021.e06872
|View full text |Cite
|
Sign up to set email alerts
|

Processing and interpretation of full tensor gravity anomalies of Southern Main Ethiopian Rift

Abstract: The study area is situated in the Southern Main Ethiopian Rift being bounded within the limit of 37 o 00″0′-38 o 50′00″E and 5 o 50′00″-7 o 00′00″N. It is well known that the complex geological structure of the Main Ethiopian Rift has attracted intense attention so far and numerous geophysical investigations have been performed using potential field data-sets in Central and Northern Main Ethiopian Rift with the exceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Directional analysis performed on the measured structures and DEM extracted lineaments presented in a rose diagrams ( Figure 4 c) and ( Figure 4 d) generally showed that dominant trend tend to run in the NE–SW in Abaya and Chamo basins and N–S direction align with the axial portions of the Tertiary Ethiopian Rift which is also in agreement with fault block geometries identified by Invariance Tensor analysis ( Figure 8 b). These results have good correlation with the faults deduced from analysis and interpretation of Full Tensor Gravity ( Kebede and Mammo, 2021 ) and known faults deduced from geological studies in the area ( Asrat et al., 2001 ; Mengesha et al., 1996 ).…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…Directional analysis performed on the measured structures and DEM extracted lineaments presented in a rose diagrams ( Figure 4 c) and ( Figure 4 d) generally showed that dominant trend tend to run in the NE–SW in Abaya and Chamo basins and N–S direction align with the axial portions of the Tertiary Ethiopian Rift which is also in agreement with fault block geometries identified by Invariance Tensor analysis ( Figure 8 b). These results have good correlation with the faults deduced from analysis and interpretation of Full Tensor Gravity ( Kebede and Mammo, 2021 ) and known faults deduced from geological studies in the area ( Asrat et al., 2001 ; Mengesha et al., 1996 ).…”
Section: Resultssupporting
confidence: 79%
“…3D Euler deconvolution technique was performing on the Bouguer gravity anomaly and Full tensor gravity components , and in an attempt to find depth to basement of lineaments. The structural index is chosen according to a prior knowledge of the source geometry of the area ( Kebede and Mammo, 2021 ), contacts like faults have a structural index of in gravity field so identifications of basement blocks faults are performed using index . Euler depth solution ( Figure 9 ) show that the limits of the crystalline basement sources running between 2500 and 3500 m deep in rift basin area where Abaya Lake, Chamo Lake and Gelana basins resides.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations